2021
DOI: 10.3390/su13126728
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological Strategies to Safeguard Insect Pollinators in Biodiversity Hotspots: Chile as a Case Study

Abstract: Industrial agriculture (IA) has been recognized among the main drivers of biodiversity loss, climate change, and native pollinator decline. Here we summarize the known negative effects of IA on pollinator biodiversity and illustrate these problems by considering the case of Chile, a “world biodiversity hotspot” (WBH) where food exports account for a considerable share of the economy in this country. Most of Chile’s WBH area is currently being replaced by IA at a fast pace, threatening local biodiversity. We pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 298 publications
(353 reference statements)
0
9
0
Order By: Relevance
“…Neonicotinoids lead to death and to a wide array of critical sub-lethal impacts in Insecta evaluated in field-realistic exposure, including alterations linked to EMMs (both in managed and wild species) [43,119,137,158,204]. These consequences led to the loss of the ecosystem services provided by these insects, including nutrient cycling and pollination [205]. These declines in local insect biodiversity have been shown to be linked to unexpected costs in agricultural production under industrialized management and impacts on the health of managed agroecosystems [206].…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonicotinoids lead to death and to a wide array of critical sub-lethal impacts in Insecta evaluated in field-realistic exposure, including alterations linked to EMMs (both in managed and wild species) [43,119,137,158,204]. These consequences led to the loss of the ecosystem services provided by these insects, including nutrient cycling and pollination [205]. These declines in local insect biodiversity have been shown to be linked to unexpected costs in agricultural production under industrialized management and impacts on the health of managed agroecosystems [206].…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%
“…This kind of research is of high importance due to the menace that declining numbers of bees and other flying insects represent for all kinds of ecosystems and for human survival [15,224]. Despite all of these problems detected in different non-target organisms, the use of neonicotinoids is currently poorly regulated, especially in developing countries [205].…”
Section: Neonicotinoid Effects On Beesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that a decrease in bacterial diversity reduces the immune response against pathogens but also affects the metabolism and degradation of carbohydrates and sugar [85]. Recently, Henríquez-Piskulich et al [86] described 44 pesticides used in Chile but banned by the European Union, all producing damage to bees. Although Chilean law demands that the farmers must notify the agricultural authority before using pesticides, this is only required when pesticides are applied near honeybee hives (Act N • 158/2015).…”
Section: Pesticidesmentioning
confidence: 99%
“…LRI, Linear retention index calculated in relation to n-alkanes. LRIb, Linear retention index already published in peer-reviewed journals and listed inPubChem(1) or Pherobase(2). When possible, the LRI was verified by a standard compound ( † ).The volatile compounds were collected in April 2018 by CLSA technique for 3 h. The compounds were identified by mass spectrometry and confirmed by linear retention indexes from the literature or laboratory standards when available.…”
mentioning
confidence: 99%